Entrepreneurial behaviour: a new perspective on the role of the HR professional. Issue 7 (4th November 2019) - Amarakoon, Upamali; Weerawardena, Jay; Verreynne, Martie-Louise; Teicher, Julian
Abstract : Purpose: The purpose of this paper is to conceptualise and validate a scale to capture entrepreneurship behaviour at the human resource management (HRM) functional level. Design/methodology/approach: Drawing from the HRM and entrepreneurship literature, this paper first conceptualises and operationalises entrepreneurial behaviour at the human resource (HR) functional level. Second, it uses a multi-phase, systematic scale development procedure to design a two-dimensional scale of entrepreneurial HRM. Finally, the scale is validated by testing its relationship with HRM innovation. Findings: The findings suggest that entrepreneurial behaviour at the HRM functional level is characterised by innovativeness, pro-activeness, risk-taking and consensus-building behaviour. The scale shed new light on the roles of HR professionals. Research limitations/implications: This paper highlights the need for HR professionals to demonstrate entrepreneurial behaviour in HRM value addition. The scale development process, while providing a detailed understanding of the entrepreneurial behaviour at the HR functional level, will facilitate future research. Practical implications: This scale provides HR professionals with the means to measure and improve entrepreneurial HRM, leading to higher levels of HRM-based value addition. Originality/value: This is the first known attempt to capture entrepreneurial behaviour at the HRM functional level.